Effect of the different substrates and organic sources on Musa propagation - Martínez, Gustavo (2021)
Introduction. The availability to have seeds in less time is an important factor in any musaceae production system. Objective. To evaluate different substrates and organic sources on the growth of banana plants and the sprouting of banana corms. Materials and methods. During 2019, in Maracay, Venezuela, two experiments were carried out in a nursery: 1) 45-day-old banana seedlings sown in: basic substrate (SB) sand and rice husk ratio 1:1(T0); SB + vermicompost ratio 1:1(T1); T1 substrate after immersion for 1 h in 50 % liquid vermicompost (Vl50%) (T2); same conditions of T2 but irrigated weekly with Vl50% (T3). Leaf number (NH), seedling height (AP), and field transplant period (PTC) were evaluated for 45 days. 2) Plantain corms sections immersed for 30 min in: water (H0); humic acid solution (FITOFOL®) (H1); Rio Caroní® humus (H2); liquid vermicompost (H3), all at 1 %, sown in a bed with soil + sand + rice husk (SAC) in a 1:1:0.25 ratio; replicated in another equal bed + 4.5 kg substrate remains for Trichoderma sp. (40,000 colony forming units) (SACT). Sprouting, AP, and root weight (PR) were evaluated during 10 weeks. Results. Experiment 1. Vermicompost significantly increased the PA by 4.5 cm and reduced the PTC from 49 to 35 days, with respect to the control. Experiment 2. Vermicompost (H3) generated highly significant differences in AP and PR with increments of 10 cm and 19 g, respectively. In interactions with SACT, FITOFOL® (H1) outperformed the other treatments. Conclusions. The liquid and/or solid vermicompost significantly accelerated the growth of banana seedlings and shortened the nursery acclimatization. H3 and FITOFOL®, combined with SACT, showed the highest AP and PR response in plantain corms.